2014
DOI: 10.1097/01.pcc.0000436198.15337.15
|View full text |Cite
|
Sign up to set email alerts
|

Sleep, Sleepiness, and Fatigue Outcomes for Parents of Critically Ill Children

Abstract: We performed a prospective observational study of 118 parents of critically ill children using objective measures of sleep and validated scales to assess fatigue and sleepiness. We found that more than a quarter of nights met criteria for acute sleep deprivation, there was considerable variability in the amount of nocturnal sleep that individual participants slept on different nights, and sleep was fragmented with a large portion of the night spent awake. Future research should focus on interventions that impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 42 publications
4
31
0
1
Order By: Relevance
“…In earlier studies, variability in sleep duration among family caregivers of critically ill children has been associated with daytime sleepiness and fatigue 28. Also documented are instability in sleep times among family caregivers of ventilator-assisted children living at home 17.…”
Section: Discussionmentioning
confidence: 97%
“…In earlier studies, variability in sleep duration among family caregivers of critically ill children has been associated with daytime sleepiness and fatigue 28. Also documented are instability in sleep times among family caregivers of ventilator-assisted children living at home 17.…”
Section: Discussionmentioning
confidence: 97%
“…Also included in the aims of the studies was the documentation of physiological, psychological and situational factors affecting fatigue among mothers (Kim et al, 2017). Other aims were as follows: prevalence estimates of self-report sleep quantity and quality among parents accommodated on the paediatric oncology ward (McLoone et al, 2013), and descriptions and measurement of sleep quantity and sleep patterns (Bevan et al, 2019;Nassery & Landgren, 2018), and additionally, factors affecting the sleep of parents with critically ill children (Stremler et al, 2014;Stremler, Haddad, Pullenayegum, & Parshuram, 2017) as well as strategies used to improve parents' sleep (Stremler, Dhukai, Wong, & Parshuram, 2011). Finally, aims also included comparisons of sleep quality and quantity among the parents who were accommodated bedside at the hospital and those who slept at a Ronald McDonald House (Franck et al, 2014).…”
Section: Aimsmentioning
confidence: 99%
“…There are some conflicting findings about parents' sleep quality in the hospitals (Table 3). In six of the studies, the parents reported poor sleep quality and disrupted and fragmented sleep during the hospitalisation (Bevan et al, 2019;Franck et al, 2014;McCann, 2008;McLoone et al, 2013;Meltzer, Davis, et al, 2012;Nassery & Landgren, 2018;Stickland et al, 2016;Stremler et al, 2014). In one study, more than half of the parents reported good sleep quality in the paediatric ward despite nocturnal awakenings (Angelhoff et al, 2017).…”
Section: Conclusion Of Findings and Recommendations Madementioning
confidence: 99%
“…23 Time spent away from other activities such as school, homemaking, and ''family time'' was assigned the national average hourly wage of a child caregiver (Can $14.61) using the market value approach regardless of the age and sex of the provider. 25,26 Statistical Analysis Descriptive statistics were used to categorize the type and value of costs expressed in 2007 Canadian dollars. The valuation of the cost model consisted of actual direct costs (with the exception of travel mileage) and estimated time costs derived from census data.…”
Section: Cost-of-illness Analysismentioning
confidence: 99%